Kształtowanie się obrazu Gepidów w źródłach antycznych i wczesnośredniowiecznych (III-VII w.) - Skibiński, Tomasz (Vox Patrum, 2020)
The article seeks to present the dynamics of the development of the image of the Gepid tribe in ancient and early medieval sources. For our analysis, we used Roman and Byzantine sources dating from the 3rd to 7th centuries.. The topic was handled in points discussing the three basic aspects of how the Gepids were perceived and presented: their manner of fighting (bravery, cruelty and using a sword as specific combat tactics), the kinship between the Gepids and the Goths, the hardness of their character, their slow movements and the infantry style of fighting (as opposed to horse fighting used by other peoples). The article presents both the above-mentioned basic elements of the tribe’s image, the changes in its perception, and the development of this image, which has gradually gained new elements derived from various traditions.